2009
DOI: 10.1016/j.jjie.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exchange rate volatility on international trade in East Asia

Abstract: JEL classification: F10 F31 N75 Keywords:Exchange rate volatility Trade East Asia a b s t r a c t Hayakawa, Kazunobu, and Kimura, Fukunari-The effect of exchange rate volatility on international trade in East AsiaIn this paper, we empirically investigate the relationship between exchange rate volatility and international trade, focusing on East Asia. Our findings are summarized as follows: first, intra-East Asian trade is discouraged by exchange rate volatility more seriously than trade in other regions. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 8 publications
2
56
1
1
Order By: Relevance
“…Thorbecke (2008) found that exchange rate volatility caused a large decline in the flow of electronic parts and components within East Asian production networks. Hayakawa and Kimura (2009) reported that exchange rate volatility significantly reduced trade in intermediate goods within East Asian production networks. Carlos Ghosen, CEO of Nissan Motor Corporation, also stated that exchange rate volatility deterred the slicing up of the value chain because it militated against long-term planning (see Crooks, 2010).…”
Section: Production Network In East Asiamentioning
confidence: 99%
“…Thorbecke (2008) found that exchange rate volatility caused a large decline in the flow of electronic parts and components within East Asian production networks. Hayakawa and Kimura (2009) reported that exchange rate volatility significantly reduced trade in intermediate goods within East Asian production networks. Carlos Ghosen, CEO of Nissan Motor Corporation, also stated that exchange rate volatility deterred the slicing up of the value chain because it militated against long-term planning (see Crooks, 2010).…”
Section: Production Network In East Asiamentioning
confidence: 99%
“…Both Thorbecke (2008) and Hayakawa and Kimura (2009) presented econometric evidence that exchange rate volatility reduces the flow of parts and components within regional trade networks. Thorbecke (2008), using DOLS estimation and annual data over the period reported that exchange rate volatility caused a large decline in the flow of parts and components within East Asian production networks.…”
Section: Impact Of Exchange Rate Volatilitymentioning
confidence: 99%
“…Thorbecke (2008), using DOLS estimation and annual data over the period reported that exchange rate volatility caused a large decline in the flow of parts and components within East Asian production networks. Hayakawa and Kimura (2009), using a gravity equation and annual data over the 1992-2005 period, found that exchange rate volatility significantly reduced trade in intermediate goods within East Asian production networks.…”
Section: Impact Of Exchange Rate Volatilitymentioning
confidence: 99%
“…It would maintain greater intraregional exchange rate stability, facilitating the flow of parts and components and FDI within regional production networks (Hayakawa and Kimura, 2009). In addition, since much East Asian trade is intra-regional, a joint appreciation against extra-regional currencies would imply much smaller appreciations of effective exchange rates (EERs) in the region.…”
Section: Rebalancing Growth In Asiamentioning
confidence: 99%